(untitled) (Journal of Hama University, 2019)
Statistical analysis was taken for 366, 302, 273, and 208 records which belong to partial milk yields in the production period of 60 ,120, 180 and 270 days respectively, between 2007 to 2010 in Al-Mukhtaria dairy cattle station(in Homs) contains a herd of Holstein cattle. (GLM)General Linear Model program which has been used to estimate fixed effects and to estimate variance component for random factors by using Restricted Maximum Likelihood (REML) for genetic parameters evaluation. Harvey program has also been used to evaluate Best Linear Unbised prediction (BLUP) for studied traits _ squares mean SE for partial milk yields in 60,120,180 and 270 days are 1185.9 29.4 ,2311.0 26.0, 3328.8 23.7 and 4559.3 21.6 kg, respectively. Season and year of calving have a highly significant effect for all studied traits. And there are significant effects (p<0.10) for parity in all triats studied. The highest milk yield in 60,120,180, and 270 days are 1151.8, 2259.9, 3247.5 and 4517.1 kg respectively in the 3rd production season. The heritability estimates for the characters mentioned before were 0.10, 0.20, 0.12, and 0.60 respectively. The highest value of the best linear unbiased prediction for sires for partial milk yield in 60 , 120 , 180 and 270 days are 17.13, 65.52, 39.52 and 8.73 kg while the lowest are -16.52 ,-42.90 ,-58.44 and -10.29 kg respectively.